Вироби з кістки та гірських порід енеоліту та бронзової доби на поселенні Фащівка - Колод, В.В.; Панковський, В.Б.; Разумов, С.М.; Корохіна, А.В. (Археологія, 2017)
У статті викладено результати структурно-сировинного, технологічного та функціонального аналізу знарядь та приладдя з поселення Фащівка, що у верхів’ях Міусу на Донецькому кряжі. Артефакти з гірських порід віднесено до енеоліту й доби пізньої бронзи. Усі кістяні вироби належать пізній бронзовій добі. Уперше подано документовані трасологічні спостереження щодо використання т. зв. тупців винятково для м’яття сириці. The paper analyzes raw materials structure, manufacture techniques, and functions in some bone and lithic tools and accessories found in 1992 at Faschivka settlement site located at the Mius river headstream in the Donets Ridge area, district Perevalsk, region of Lugansk. The objects of bone comprise the horse metatarsal skate of the «Sadchikovskiy» type, the notched cattle rib scraper, and the cattle mandibulae breakers. These all were attributed here to the late phase of the Berezhnovka-Maiovka culture (14th-13th c. BC) or, possibly, to the very end of the Late Bronze Age (12th-10th c. BC). It turned out that mandibulae breakers have been used exclusively in finishing rawhides and not in fleshing skins as such tools were usually thought. The Chalcolithic artefacts, presumably of the Strilcha Skelia culture (4600-4300 cal BC), are made of dark grey translucent flint of the Upper Cretaceous origin. These include the knife burin, scraper-rasp-planing knife, the planing knife, the end-side scraper, the cutting flake and blade tools, and a blade fragment. The Late Bronze Age «sling stones» were made of a different sort of light grey opaque flint. The rest of the LBA kit consists of axe hammer, hammer, disk-shaped object, grindstone, and quern-stone, all made of serpentinite and lime- or sandstone materials. Изложены результаты структурно-сырьевого, технологического и функционального анализа орудий и приспособлений из поселения Фащевка (верховья Миуса на Донецком кряже; Перевальский р-н Луганской обл.). Все костяные изделия (конек типа «Садчиковский», зубчатый скребок и тупики) относятся ко второму этапу бережновско-маевской срубной культуры (XIV—XIII вв. до н. э.) или, не исключено, к постсрубному времени (XII—X вв. до н. э.). Выяснилось, что тупики применялись исключительно для разминания кожи, а не для мездрения шкур. Семь артефактов из верхнемелового темно-серого полупрозрачного кремня относятся к скелянской культуре энеолита (4600—4300 гг. до н. е.). Это нож-перфоратор, скребок-скобель-строгальный нож, строгальный нож, концебоковой скребок, режущие орудия на отщепе и пластине, фрагмент пластины. Кремень двух «пращевых камней» эпохи поздней бронзы иной — светло-серый непрозрачный. Прочие изделия (топор-молот, молот, диск, точило, зернотерка) выполнены из серпентинита, известняка и песчаника.